MEMPERTEMUKAN HIPER-REALITAS DAN REFRACTIONS OF DURÉÉ : Pembacaan Multi-NaratifVisual dalam Film Simone dan Film Inception - Rosa, Dien Vidia (Seni Media Rekam ISI Surakarta, 2017)
Film realities emerged in multifacet.Two interesting concepts that were tried to be presented in the article were hypereality and refraction of duréé. Both were consequences of digitalization that refered to the rose of virtual space and beyond subject's consciousness.Both also effected audiens consciousness positioning to reality which was appeared. The encounter of those concepts was discussed in images power discourse. By using Barthes's semiology method tocrack and decode visual narative element of film, reality exploration was seen as signs playing and images ideology.Keywords : Hiper-realitas,refractions of duréé,multi-naratif visual film